Transformative Integration of Interdisciplinary Knowledge and Ogoh-Ogoh Symbolism in Cultivating Social Harmony in Mataram - Ratnadewi, Ni Luh Sinar Ayu; Wiguna, Ida Bagus Alit Arta (Jayapangus Press, 2025)
Mataram City, as the center of religious, ethnic, and cultural diversity in West Nusa Tenggara Province, presents its challenges in building inclusive and sustainable social harmony. One of the symbols of local culture that plays a role in maintaining this harmony is Ogoh-Ogoh, which, although it originated from Hindu religious traditions, has now become a space for cross-identity interaction. This research aims to examine how Ogoh-Ogoh symbolism is understood and interpreted in the context of a multicultural society, as well as its contribution to the formation of harmony between religious communities. The method used is qualitative with an interdisciplinary approach, combining insights from cultural anthropology, social psychology, and religious studies. Data was obtained through participatory observation, in-depth interviews, and community discussions, then analyzed using thematic coding techniques. The results of the study show that Ogoh-Ogoh has undergone a transformation in meaning, from a religious symbol to a means of social education that is able to build a collective awareness of the importance of tolerance and togetherness. The participation of interfaith communities in the Ogoh-Ogoh tradition strengthens social cohesion and shows the potential of local culture as an integrative medium. However, there is still resistance from conservative groups who view Ogoh-Ogoh exclusively, so an interdisciplinary, inclusive, and participatory approach is needed in the management of this cultural symbol. This study concludes that Ogoh-Ogoh is a dynamic symbol that can make a real contribution to strengthening social harmony if interpreted openly and across identity boundaries.